Circumstances short of global war: British defence, colonial internal security, and decolonisation in Kenya, 1945-65 - Percox, David A. (2001)
This thesis fills a significant gap in current secondary literature on post-war British defence and internal security policy. Hitherto, post-war British defence policy in Kenya has only been considered in passing, in relation to the larger question of Middle East strategy. Very little attention has been paid to Kenya's particular importance in the post-1956 ‘east of Suez’ role. Current works on British internal security policy in Kenya concentrate either on post-war policing in general or, more specifically, on the British counter-insurgency campaign during the Mau Mau revolt (1952-6).